Treatment-related decisional conflict in pre-dialysis chronic kidney disease patients in Singapore: prevalence and determinants - Goh, Zack Zhong Sheng (2022)
Background. In advanced chronic kidney disease (CKD), patients face complex decisions related to renal replacement modality that can cause decisional conflict and delay. This study aimed to evaluate the prevalence of severe decisional conflict across decision types and to identify the psychosocial and clinical factors associated with decisional conflict in this population. Design. Observational cross-sectional study. Methods. Patients with CKD in renal care were recruited. The Decisional Conflict Scale (DCS), Functional, Communicative, and Critical Health Literacy (FCCHL), Health Literacy Questionnaire (HLQ), Hospital Anxiety and Depression Scale (HADS), Brief Illness Perception Questionnaire (BIPQ), and the Kidney-disease Quality of Life (KDQOL)questionnaires were used. Clinical data were obtained from medical records. Bivariate and multivariable logistic regression models were used to identify predictors of severe decisional conflict (DCS score ≥ 37.5). Results. Participants (N = 190; response rate = 56.7%; mean age = 62.8 ± 10.8) reported moderate levels of decisional conflict (29.7 ± 14.5). The overall prevalence of severe decisional conflict was 27.5% (n = 46) with no significant differences across decision types (dialysis, modality, access). Ethnicity (Chinese), marital status (married), BIPQ treatment control, coherence, KDQOL staff encouragement, and all health literacy domains, except functional health literacy, were significant predictors of decisional conflict in the unadjusted models. In the multivariable model, only the health literacy domains of FCCHL Communicative, and HLQ Active Engagement remained significant. Conclusion. Even after pre-dialysis education, many CKD patients in this study still report severe decisional conflict, with rates remaining substantial across decision junctures. The associations of decisional conflict and health literacy skills related to communication and engagement with healthcare providers indicate that more collaborative and patient-centric pre-dialysis programs may support patient activation and resolve decisional conflict.